Cargo Delivery web-based Application with Ant Colony Optimization Algorithm for Shortest Route search: A Case Study in the Die Cutting Industry - Wiratama, Jansen; Wijaya, Santo Fernandi; Tandika, Idris; Santoso, Hari (Universitas Merdeka Malang, 2024)
Conventional business processes sometimes lead to negligence and forgetfulness regarding important delivery requests, thereby causing operational disruptions that could impact the company's reputation. The limitations of conventional methods are also faced by CV Karya Pelangi, a company operating in the Die die-cutting industry, where many customer orders are usually submitted orally, causing problems that lead to late deliveries and delays in the production process. This problem is exacerbated by limited resources, for example, a delivery fleet consisting of only two drivers. Focuses on developing web-based applications with prototyping models and implementing the Ant Colony Optimization (ACO) algorithm to overcome delivery route optimization challenges. This research produces a web-based application using a software prototype model. In addition to applying the ACO algorithm to identify optimal delivery routes, the app offers insights into the goods transported, shipper details, and departure and destination times. Simulation results show that CV Karya Pelangi can now determine short circuit paths efficiently, thereby increasing operational efficiency, with a path length of 0.3892 and a pheromone intensity of 2.569. This innovative solution promises to revolutionize cargo shipping operations, ensuring timely and efficient deliveries increasing customer satisfaction and operational efficiency.